Relocatable modular capacities in risk aware strategic supply network planning under demand uncertainty - Ariane Kayser; Florian Sahling (Schmalenbach Journal of Business Research (SBUR), 2023)
We propose a new model formulation for a three-echelon supply network design problem incorporating the concept of relocatable modular capacities. A robust supply network configuration must be determined based on uncertain demand. Furthermore, by incorporating the conditional value at risk (CVaR), the risk induced by uncertain demand is explicitly considered. The derived supply network configuration should maximize the weighted sum of the expected net present value and the CVaR. The resulting nonlinear model formulation is approximated by a piecewise linearization. Our numerical investigation shows that the derived supply network configuration is robust and stable in the presence of uncertain demand.
Keywords: 650; Supply network reconfiguration; Modular capacities; Stochastic demand; Conditional value at risk